Phytochemical analysis and antioxidant activity of Haloxylon salicarnicum, Ochradenus arabicus and Tamarix nilotica - Alshamsi, Mariam M. A.; Alnuaimi, Alghazal K. H.; Alshamsi, Reema M. S.; Senthilkumar, A.; Karthishwaran, K.; Al-Zayadneh, Wasef A. W.; Cheruth, Abdul J. (Journal of Phytology, 2019)
In the present investigation, the preliminary phytochemical analysis and antioxidant potential of hexane, chloroform, acetone and methanol extracts of Haloxylon salicarnicum, Ochradenus arabicus and Tamarix nilotica were reported. The presence of flavonoid, alkaloid, phenols, terpenoids, carbohydrate, tannin, protein, steroids, saponin, phlobatannin, cardiacglycoside, anthraquinines and volatile oils were determined and for antioxidant activity, DPPH, ABTS, superoxide anion radical and hydroxyl radical scavenging potential were studied. Strong presence of alkaloid, tannin, steroids in H. salicarnicum, flavonoid and phenols in O. arabicus and saponin T. nilotica were observed. In the present investigation, all the extracts inhibited the free radicals the methanol extract of O. arabicus was identified as potential crude extract compared to all other extracts with the IC50 values of 91.65 (DPPH), 94.62 (ABTS), 95.82 (O2) and 96.02 (OH) µg/mL. Whereas, the IC50 value of the standard, Gallic acid were 125.25 (DPPH), 142.32 (ABTS), 130.78 (O2) and 139.93 µg/mL (OH). Whereas, the IC50 value of the standard, Gallic acid were 125.25 (DPPH), 142.32 (ABTS), 130.78 (O2) and 139.93 µg/mL (OH)The present study suggests that methanol extract of O. arabicus can be used for the isolation potential natural antioxidant.